Analysis of Genetic Heterogeneity in Chlamydia trachomatis Clinical Isolates of Serovars D, E, and F by Amplified Fragment Length Polymorphism - Morré, Servaas A. (American Society for Microbiology, 2000)
Amplified fragment length polymorphism (AFLP) fingerprinting of clinical isolates of Chlamydia trachomatis serovars D, E, and F showed a low percentage of genetic heterogeneity, but clear differences were found. Isolates from index patients and partners had identical AFLP patterns and AFLP markers. Characterization of these AFLP markers could give more insight into the differences in virulence and clinical course of C. trachomatis infections.